PENGARUH PENGENDALIAN INTERNAL, KEJELASAN SASARAN ANGGARAN, DAN PERGANTIAN KEPALA SKPD TERHADAP AKUNTABILITAS KINERJA - Manullang, Surya Benediktus; Abdullah, Syukriy (Jurnal Ilmiah Mahasiswa Ekonomi Akuntansi, 2019)
The purpoese of this study was to determine the effect of internal controls (PI), budget clarity (KSA) and the change of head of agency (PKS) on performance accountability (AK) at agencies of North Sumatera Province for Fiscal Year 2017. Samples in this study is at least 3 employees who perform accounting functions or use of budgets at 41 unit of the agencies in the Province of North Sumatera, so that obtained 60 observations. Data were analyzed by using multiple regression analysis with the help of SPSS program. The data used in the primary data in the form of interviews and giving questionnaires to employees. The result of the research shows that (1) internal control (PI) has influence to performance accountability (AK) with positive influence, (2) budget clarity (KSA) has positive effect on performance accountability (AK), (3) changed of head of agency (PKS) have negative effect on performance accountability (AK).